Versatile Pedagogical and Social Activities of a Graduate of Riga Polytechnic Institute Jānis Stiprais (1870–1946) - Zigmunde, Alīda; Stikute, Elita (History of Engineering Sciences and Institutions of Higher Education, 2021)
The research discusses continuous effort of a pedagogue, economist and journalist Jānis Stiprais (1870–1946) in his pursuit to obtain education and his versatile pedagogical activities in Tomsk (Russia), Tukums, Valka and Riga, as well as the contribution he made in such areas as journalism, folklore and social work. J. Stiprais shared his knowledge of economics gained at Riga Polytechnic Institute (RPI) with the students at the University of Latvia (UL), Latvia People’s University and Vilis Olavs Commercial School; in the first half of the 20th century he was the principal of educational institutions in Tukums, Valka and Riga, he also was one of the signatories of the Memorandum of the Central Council of Latvia on 17 March 1944. In the recognition of J. Stiprais merit for Latvia, he was honoured with the highest award of the Republic of Latvia – the Order of the Three Stars.